Hydrogen Peroxide-Based Fluorometric Assay for Real-Time Monitoring of SAM-Dependent Methyltransferases - Akhtar, M. Kalim; Vijay, Dhanya; Umbreen, Saima; McLean, Chris J.; Cai, Yizhi; Campopiano, Dominic J.; Loake, Gary J. (Frontiers in Bioengineering and Biotechnology, 2018)
Methylated chemicals are widely used as key intermediates for the syntheses of pharmaceuticals, fragrances, flavours, biofuels and plastics. In nature, the process of methylation is commonly undertaken by a super-family of S-adenosyl methionine-dependent enzymes known as methyltransferases. Herein, we describe a novel high throughput enzyme-coupled assay for determining methyltransferase activites. Adenosylhomocysteine nucleosidase, xanthine oxidase, and horseradish peroxidase enzymes were shown to function in tandem to generate a fluorescence signal in the presence of S-adenosyl-L-homocysteine and Amplex Red (10-acetyl-3,7-dihydroxyphenoxazine). Since S-adenosyl-L-homocysteine is a key by-product of reactions catalysed by S-adenosyl methionine-dependent methyltransferases, these enzymes were used in a coupling fashion to assess the activities of EcoRI methyltransferase and a salicylic acid methyltransferase from Clarkia breweri in the presence of S-adenosyl methionine. For the EcoRI methyltransferase, the assay was sensitive enough to allow the monitoring of DNA methylation in the nanomolar range. In the case of the salicylic acid methyltransferase, detectable activity was observed for several substrates including salicylic acid, benzoic acid, 3-hydroxybenzoic acid, and vanillic acid. Additionally, the de novo synthesis of the relatively expensive and unstable cosubstrate, S-adenosyl methionine, catalysed by methionine adenosyltransferase could be incorporated within the assay. Overall, the assay offers an excellent level of sensitivity that permits continuous and reliable monitoring of methyltransferase activities. We anticipate this assay will serve as a useful bioanalytical tool for the rapid screening of S-adenosyl methionine-dependent methyltransferase activities.